Identification of Somatotopic Organization and Optimal Stimulation Site Within the Subthalamic Nucleus for Parkinson's Disease. Issue 3 (16th November 2018) - Sasaki, Tatsuya; Kuwahara, Ken; Kin, Ittetsu; Okazaki, Mihoko; Sasada, Susumu; Shinko, Aiko; Kameda, Masahiro; Yasuhara, Takao; Agari, Takashi; Date, Isao
Abstract: BACKGROUND: Details of the somatotopy within the subthalamic nucleus (STN) are still poorly understood; however, the STN is a common target of deep brain stimulation (DBS) for Parkinson disease. OBJECTIVE: To examine somatotopic organization within the STN and identify optimal stimulation sites from 77 surgical cases with microelectrode recording. METHODS: STN-DBS was performed for 77 patients with Parkinson disease between 2010 and 2014. We performed passive movements of each joint and captured single neuronal activities to identify movement-related cells (MRCs). The sites of MRCs and active contacts were determined by measuring their distances from the first contact of DBS electrode. Their positional correlations were directly and indirectly analyzed. RESULTS: The number of obtained MRCs was 264, of which 151 responded to multiple joints. The average x -, y -, and z -coordinates of the cells of the upper and lower limbs from the midcommisural point were 13.1 ± 1.1 and 12.7 ± 1.2, 0.22 ± 1.3 and −0.45 ± 1.5, and −2.5 ± 1.1 and −3.0 ± 1.4 mm, respectively. Most MRCs were distributed in the upper third of the STN, in its superior, lateral, and posterior regions, along the DBS electrode routes. Active contacts were observed to lie slightly inferior, medial, and posterior to the average MRC position. CONCLUSION: Somatotopic organization of the STN was easier to observe in the present study than in previous studies. Optimal stimulation sites were located inferior, medial, and posterior to the average MRC location. The sites may correspond to associative or motor parts through which fibers from the supplementary motor area pass.